PROSPECTIVE TEACHERS CONCEPTION OF MATHEMATICAL CREATIVE THINKING - Purwosetiyono, Fransiskus Xaverius Didik; Sa'dijah, Cholis; Hidayanto, Erry; Chandra, Tjang Daniel; As'ari, Abdur Rahman; Irawan, Edy Bambang (Universitas Negeri Malang, 2018)
The purpose of this study was to describe the initial conception of prospective teachers about creative thinking in mathematics. This research used a qualitative research method. The Research was conducted at private universities in Semarang, held in the second semester of the academic year 2016/2017. The subjects were six students of the seventh semester. This research used two instruments; test to explore the concept of creative thinking and interview. This study provides findings that there are similarities in the concept of prospective teachers in mathematical creative thinking. The prospective teacher's conception of the creative thinking of mathematics leads to the emergence of new concepts or ideas in completing mathematical problems based on experience. The appearance of the new idea in question is to solve a different problem from the existing procedure and solve the problem with a different perspective that is still logical. The prospective teacher's said that it was necessary for prospective teachers to understand the concept of creative thinking in mathematics to solve mathematical problems from various perspectives based on his learning experience.